Constrain the SED Type of Unidentified Fermi Objects - An-Li Tsai; Yuji Urata; Satoko Takahashi; Chia-Jung Chuang (Journal of Astronomy and Space Sciences, 2013)
2FGL J1823.8+4312 and 2FGL J1304.1-2415 are two unidentified Fermi objects which are associated with cluster of galaxies. In order to exam the possibility of cluster of galaxies as gamma-ray emitters, we search for counterpart of these two unidentified Fermi objects in other wavebands. However, we find other candidate to be more likely the counterpart of the unidentified Fermi object for both sources. We compare their light curves and SEDs in order to identify their source types. However, data at millimeter and sub-millimeter wavebands, which is important for us to constrain the SED at synchrotron peak, is lacking of measurement. Therefore, we proposed to SMA observation for these two sources. We have got data and are doing further analysis.